PRINSIP TATA KELOLA DAN PERUBAHAN PARADIGMA PENGELOLAAN BUMN DALAM UU NO. 1 TAHUN 2025 - Agustinus Nugroho Jati; Gunawan Widjaja; Dyah Ersita Yustanti (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study discusses the principles of governance and paradigm shifts in the management of State-Owned Enterprises (SOEs) based on Law No. 1 of 2025. This law is a milestone in the reform of SOE management, shifting the old bureaucratic paradigm towards a modern corporate model that is professional, efficient, and accountable. The governance principles emphasise transparency, accountability, independence, and fairness as the foundation for carrying out the business and social functions of SOEs. The separation of SOE finances from the State Budget (APBN) and the recognition of SOEs as private legal entities require more professional management with the state acting as an investor. This study uses a literature review method to analyse the legal, economic, and governance aspects of the law. The findings indicate that this paradigm shift brings new dynamics to SOE management, which is expected to enhance their competitiveness and contribution to sustainable national development. The success of implementation depends on the consistency of regulations, oversight mechanisms, and the professionalism of SOE managers.